Raman Spectroscopy of Graphene/CNT Layers Deposited on Interdigit Sensors for Application in Gas Detection - Stefan-Marian Iordache; Ana-Maria Iordache; Ana-Maria Florea (Raduta); Stefan Caramizoiu; Catalin Parvulescu; Flaviu Baiasu; Irina Negut; Bogdan Bita (C)
Graphene/CNT layers were deposited onto platinum electrodes of an interdigitated sensor using radio-frequency magnetron sputtering. The graphene/CNTs were synthesized in an Argon atmosphere at a pressure of (2 × 10−2–5 × 10−3) mbar, with the substrate maintained at 300 °C either through continuous heating with an electronically controlled heater or by applying a −200 V bias using a direct current power supply throughout the deposition process. The study compares the surface morphology, carbon atom arrangement within the layer volumes, and electrical properties of the films as influenced by the different methods of substrate heating. X-ray diffraction and Raman spectroscopy confirmed the formation of CNTs within the graphene matrix. Additionally, scanning electron microscopy revealed that the carbon nanotubes are aligned and organized into cluster-like structure. The graphene/CNT layers produced at higher pressures present exponential I–V characteristics that ascertain the semiconducting character of the layers and their suitability for applications in gas sensing.